Motile sperm organelle morphology examination (MSOME): intervariation study of normal sperm and sperm with large nuclear vacuoles - Baruffi Ricardo LR; Massaro Fabiana C; Petersen Claudia G; Oliveira João Batista A; Mauri Ana L; Silva Liliane FI; Ricci Juliana; Franco José G (BMC, 2010)
Abstract Background Although the motile sperm organelle morphology examination (MSOME) was developed only as a selection criterion, its application as a method for classifying sperm morphology may represent an improvement in evaluation of semen quality, with potential clinical repercussions. The present study aimed to evaluate individual variations in the motile sperm organelle morphology examination (MSOME) analysis after a time interval. Methods Two semen samples were obtained from 240 men from an unselected group of couples undergoing infertility investigation and treatment. Mean time interval between the two semen evaluations was 119 +/- 102 days. No clinical or surgical treatment was realized between the two observations. Spermatozoa were analyzed at greater than or equal to 8400× magnification by inverted microscope equipped with DIC/Nomarski differential interference contrast optics. At least 200 motile spermatozoa per semen sample were evaluated and percentages of normal spermatozoa and spermatozoa with large nuclear vacuoles (LNV/one or more vacuoles occupying >50% of the sperm nuclear area) were determined. A spermatozoon was classified as morphologically normal when it exhibited a normal nucleus (smooth, symmetric and oval nucleus, width 3.28 +/- 0.20 μm, length 4.75 +/- 0.20 μm/absence of vacuoles occupying >4% of nuclear area) as well as acrosome, post-acrosomal lamina, neck and tail, besides not presenting cytoplasm around the head. One examiner, blinded to subject identity, performed the entire study. Results Mean percentages of morphologically normal and LNV spermatozoa were identical in the two MSOME analyses (1.6 +/- 2.2% vs. 1.6 +/- 2.1% P = 0.83 and 25.2 +/- 19.2% vs. 26.1 +/- 19.0% P = 0.31, respectively). Regression analysis between the two samples revealed significant positive correlation for morphologically normal and for LNV spermatozoa (r = 0.57 95% CI:0.47-0.65 P < 0.0001 and r = 0.50 95% CI:0.38-0.58 P < 0.0001, respectively). Conclusions The significant positive correlation and absence of differences between two sperm samples evaluated after a time interval with respect to normal morphology and LNV spermatozoa indicated that MSOME seems reliable (at least for these two specific sperm forms) for analyzing semen. The present result supports the future use of MSOME as a routine method for semen analysis.